RETRACTED: Principles of efficient and innovative use of disorder plants in interior solutions of dining facilities - Abdullayev A.M.; Jonuzakov A.E.; Abdusamat N.I.; Quldoshev E.N.; Narziyev A.Q.; Abdusamatova L.X. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001